A fence-line contrast reveals effects of grazing on communities of plants and ground-dwelling arthropods in a Mongolian grassland. (August 2022) - Nishimura, Issei; Iwachido, Yuki; Nambu, Misa; Sasaki, Takehiro
Abstract: Livestock grazing is the main land use in grasslands and a major driver of change in grassland ecosystems. Previous studies have examined the effects of grazing on plant communities; however, grazing effects on ground-dwelling arthropod communities remain unclear. In this study, we examined the effects of livestock grazing on plant communities (plant species richness, functional diversity, and functional trait composition) and ground-dwelling arthropods (total abundance, order-level abundance, and feeding guild-level abundance) using a fence-line contrast in a Mongolian grassland. The grazing effects on plant communities were observed in plant height, leaf area, and leaf dry matter content, which may be due to the variation of grazing resistance among plant species and livestock preferences. The effects of grazing on arthropod communities were different among orders and feeding guilds. Our findings complement and reinforce previous findings that utilized fence-line contrasts. Highlights: Grazing altered plant functional trait composition. Total abundance of ground-dwelling arthropods was not affected by grazing. Grazing effects on ground-dwelling arthropods varied among orders and guilds.